(untitled) (The Journal of Plant Protection Sciences, 2021)
Bactrocera cucurbitae (Coq.) is considered as a serious pest of pointed gourd. Peak incidence of it was obtained in third week of May to first week of June during all the three years of study (i.e. 2007-08, 2008-09, 2009-10). Studies on biology showed that the incubation, larval, pupal and adult longevity periods were 2 to 5 days, 5 to 7 days, 6 to 9 days, 37 to 41 days in June-July and 4 to 6 days, 16 to 19 days, 17 to 21 days, 23 to 32 days in August-October, respectively. Correlation with individual weather factors revealed that each of maximum and minimum temperature had significant positive correlation (r = +0.386 and +0.501, respectively) on the population build up of the pest. The relative humidity % of morning hours had significantly negative correlation (r = -0.451) and that of evening slightly positive (r = +0.284). Rainfall had insignificantly positive (r = +0.195), soil temperature significantly positive (r = +0.555) and the bright sun shine hours insignificantly positive (r = +0.103) effects on the population development.